A feasibility study for the provision of electronic healthcare tools and services in areas of Greece, Cyprus and Italy - Mougiakakou, Stavroula Gr; Kyriacou, Efthyvoulos C.; Perakis, Kostas; Papadopoulos, Homer; Androulidakis, Aggelos; Konnis, Georgios; Tranfaglia, Riccardo; Pecchia, Leandro; Bracale, Umberto; Pattichis, Constantinos S.; Koutsouris, Dimitrios (My University, 2011)
Through this paper, we present the initial steps for the creation of an integrated platform for the provision of a series of eHealth tools and services to both citizens and travelers in isolated areas of thesoutheast Mediterranean, and on board ships travelling across it. The platform was created through an INTERREG IIIB ARCHIMED project called INTERMED